Workshops “Historical and typological approaches to Baltic morphosyntax” (Vilnius, April 2016) and “Language contact and language change in the Baltic States and Switzerland” (Zürich, September 2016) - Villanueva Svensson, Miguel (Baltistica, 2016)
–